Avaliação do uso de RPA quadrimotor para aplicações de mapeamento - Lopes, Thiago (Universidade Federal de São Carlos, 2019)
As a result of the popularization of the technology of the Remotely Aircraft (RPAs) and of the Legislation recently issued by ANAC (National Civil Aviation Agency) that regulates the use of these for commercial purposes, there is an imminent tendency of growth in the acquisition of such equipment and a dissemination of the techniques for the most varied uses. This research intends to analyze the use of Remotely Piloted Aircraft in aerophotogrammetric surveys for mapping areas, thus verifying the quality, consistency and accuracy of the data obtained and looking to generate three - dimensional models of representation that surely correspond to the surface of the area in question. Thus, with the confirmation of this accuracy, it is possible to indicate each type of use of this data in order to propose new regulations and acceptance of this mapping technique.
RPA quadrimotor evaluation for mapping applications
Keywords: RPA; Aerofotogrametria; Mapeamento; Legislação; Comercial; RPA; Aerophotogrammetry; Mapping; Legislation; Commercial; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL